Brief Report: Isogenic Induced Pluripotent Stem Cell Lines From an Adult With Mosaic Down Syndrome Model Accelerated Neuronal Ageing and Neurodegeneration. (June 2015) - Murray, Aoife; Letourneau, Audrey; Canzonetta, Claudia; Stathaki, Elisavet; Gimelli, Stefania; Sloan‐Bena, Frederique; Abrehart, Robert; Goh, Pollyanna; Lim, Shuhui; Baldo, Chiara; Dagna‐Bricarelli, Franca; Hannan, Saad; et al.
Abstract Trisomy 21 (T21), Down Syndrome (DS) is the most common genetic cause of dementia and intellectual disability. Modeling DS is beginning to yield pharmaceutical therapeutic interventions for amelioration of intellectual disability, which are currently being tested in clinical trials. DS is also a unique genetic system for investigation of pathological and protective mechanisms for accelerated ageing, neurodegeneration, dementia, cancer, and other important common diseases. New drugs could be identified and disease mechanisms better understood by establishment of well‐controlled cell model systems. We have developed a first nonintegration‐reprogrammed isogenic human induced pluripotent stem cell (iPSC) model of DS by reprogramming the skin fibroblasts from an adult individual with constitutional mosaicism for DS and separately cloning multiple isogenic T21 and euploid (D21) iPSC lines. Our model shows a very low number of reprogramming rearrangements as assessed by a high‐resolution whole genome CGH‐array hybridization, and it reproduces several cellular pathologies seen in primary human DS cells, as assessed by automated high‐content microscopic analysis. Early differentiation shows an imbalance of the lineage‐specific stem/progenitor cell compartments: T21 causes slower proliferation of neural and faster expansion of hematopoietic lineage. T21 iPSC‐derived neurons show increased production of amyloid peptide‐containing material, a decrease in mitochondrial membrane potential, and an increased number and abnormal appearance of mitochondria. Finally, T21‐derived neurons show significantly higher number of DNA double‐strand breaks than isogenic D21 controls. Our fully isogenic system therefore opens possibilities for modeling mechanisms of developmental, accelerated ageing, and neurodegenerative pathologies caused by T21. Stem Cells2015;33:2077–2084